An Empirical Examination of Artificial Intelligence Adoption and Its Influence on Business Outcomes in Indian Start-Ups - Kulkarni, Akanksha Abhijit (Digital Repository of Theses, 2025)
This research investigates the transformative role of Artificial Intelligence (AI) in the entrepreneurial and innovation landscape of Indian start-ups through the development and application of advanced analytical frameworks. It addresses the complex interplay between AI adoption, innovation outcomes, and operational efficiency by integrating heterogeneous data sources, encompassing quantitative firm-level performance metrics, qualitative survey responses, and industry-specific characteristics. It proposes a suite of novel, methodologically rigorous approaches tailored to capture latent constructs, infer causal relationships, model dynamic diffusion patterns, support multi-criteria strategic decisions, and synthesize multi-modal data. The collective objective is to deliver robust empirical insights and actionable frameworks that facilitate practical guidance for AI-driven entrepreneurship. The Multi-Stage Hierarchical Bayesian Latent Variable Model (MS-HBLVM), estimates unobserved elements like adoption intensity, innovation outcomes, efficiency improvements across sectors. This probabilistic model incorporates uncertainty and variation through Markov Chain Monte Carlo techniques. To move from association to causation, Explainable Causal Graphical Modeling with Counterfactual Analysis (ECGM-CA) is applied, enabling the construction of directed causal pathways and simulated scenarios comparing firms with and without AI adoption. Dynamic Temporal Network Analysis (DTNA-AT) captures AI adoption spread over time. An Adaptive Multi-Criteria Decision-Making model with Fuzzy Cognitive Maps (AMCDM-FCM), integrates expert judgment and firm data to assess competing adoption strategies. An Integrated Multi-Modal Deep Embedding Framework (IMDEF) employs deep learning to combine survey responses, performance indicators, and interview narratives, allowing for clustering of firms and detection of unusual adoption behaviors. Findings suggest AI adoption carries an 85% likelihood of improving operational efficiency by more than 15%. Causal estimation suggests that AI raises revenue growth by around 18%, while counterfactual analysis indicates efficiency could decline by 10% in the absence of adoption. In summary, this research contributes a comprehensive methodological toolkit for examining the multifaceted applications of AI in entrepreneurship and innovation. By employing a combination of varied methodologies this study addresses both theoretical and practical dimensions of AI integration in Indian start-ups. The findings advance empirical knowledge underscoring the critical role of AI as an innovation enabler and growth catalyst in emerging entrepreneurial ecosystems. The methodological innovations presented herein serve as a blueprint for future interdisciplinary research. Keywords: artificial intelligence, start-ups, business performance, technology adoption, innovation, India